Intrighi macabri: Alla scoperta dell’accento ungherese nel parlare l’italiano - Huszthy, Bálint (Verbum – Analecta Neolatina, 2016)
Hungarians who speak Italian fluently usually commit several pronunciation mistakes. These mistakes go unnoticed, even by native Italians because of the extreme dialectal fragmentation of Italian. However, the recurrent phonetic and phonological features of the Hungarian foreign accent show great differences compared to any Italian varieties. The aim of this paper is to collect and analyse the most common phonetic and phonological characteristics of the foreign accent of Hungarians while speaking Italian, and possibly help them avoid the most obvious mistakes, or, where it is not possible, at least make them realise the Hungarian aspects of their speech that affect their pronunciation of Italian.